Treatment With Cytarabine at Initiation of Therapy With Cyclosporine and Glucocorticoids for Dogs With Meningoencephalomyelitis of Unknown Origin Is Not Associated With Improved Outcomes - Barber, Renee; Downey Koos, Lauren (Frontiers in Veterinary Science, 2022)
Meningoencephalomyelitis of unknown origin (MUO) is a common disorder of dogs that results in significant morbidity and mortality. The ideal treatment regimen is not known but a second immunosuppressive agent is often utilized in combination with glucocorticoids to increase efficacy and reduce side effects. Recently, a benefit to using a cytosine arabinoside (CA) constant rate infusion (CRI) at the time of diagnosis has been demonstrated. Here, a retrospective study was performed to determine if administration of CA at the time of diagnosis would alter prognosis in dogs receiving cyclosporine and prednisone for treatment of MUO. Medical records of 51 client-owned dogs diagnosed with MUO at one institution were reviewed (2009-2019). All dogs were treated with cyclosporine and a tapering course of prednisone. Twenty-one dogs received a single initial 200 mg/m2 treatment with CA either as a CRI or subcutaneously. Significantly more patients in the CA treatment group were obtunded on presentation but all other baseline parameters were similar between groups. No differences in success (defined as sustained improvement on neurological exam with owner perceived good quality of life), relapse, or death were identified at 1-, 3-, 6-, 9-, 12-, 18-, or 36-month time points. These results do not support treatment with CA (either as a CRI or subcutaneously) at the time of diagnosis in dogs treated with cyclosporine and prednisone.